2015
DOI: 10.1088/0004-637x/810/1/33
|View full text |Cite
|
Sign up to set email alerts
|

The Turbulence Velocity Power Spectrum of Neutral Hydrogen in the Small Magellanic Cloud

Abstract: We present the results of the Velocity Coordinate Spectrum (VCS) technique to calculate the velocity power spectrum of turbulence in the Small Magellanic Cloud (SMC) in 21 cm emission. We present an updated version of the VCS technique that takes into account regular motions, which is an important factor in our SMC VCS analysis. We have obtained a velocity spectral index of −3.85, a cold phase sonic Mach number of 5.6, and an injection scale of 2.3 kpc. The spectral index is steeper than the Kolmogorov index, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 49 publications
3
64
0
Order By: Relevance
“…In external galaxies, the driving scale can be estimated by measuring the ISM velocity power spectrum, for example using HI gas observations (e.g. Chepurnov et al 2015). Martizzi et al (2015) derived a simple estimate of the turbulent velocity dispersion produced by SNe feedback as a function of mean ambient density and volumetric SN rate, and showed that it agreed with simulations of multiple SNe in a periodic box.…”
Section: Results Of the Energetics Analysismentioning
confidence: 99%
“…In external galaxies, the driving scale can be estimated by measuring the ISM velocity power spectrum, for example using HI gas observations (e.g. Chepurnov et al 2015). Martizzi et al (2015) derived a simple estimate of the turbulent velocity dispersion produced by SNe feedback as a function of mean ambient density and volumetric SN rate, and showed that it agreed with simulations of multiple SNe in a periodic box.…”
Section: Results Of the Energetics Analysismentioning
confidence: 99%
“…tral lines (see Chepurnov et al 2010Chepurnov et al , 2015 or synchrotron emission (see Lazarian & Pogosyan 2012, 2016, while the Alfven Mach number M A can be obtained using anisotropy studies with spectral lines (see Esquivel & Lazarian 2005, Burkhart et al 2014, Esquivel, Lazarian & Pogosyan 2015 or synchrotron studies (see Lazarian & Pogosyan 2012, 2016, Herron et al 2016. In particular the variations of L and M A with the distance from the observer can be obtained using multifrequency polarization studies as explained in Lazarian & Pogosyan (2016).…”
Section: Streaming Of Crs In Galaxiesmentioning
confidence: 99%
“…Widely-used evidence of the turbulence in the ISM is seen in the so-called Big Power Law in the Sky (Armstrong et al 1995;Chepurnov & Lazarian 2010) that reflects the Kolmogorov spectrum of electron density fluctuations, in nonthermal Doppler broadening (see Draine 2011), in the power-law scalings of the fluctuations measured in Position-Position Velocity (PPV) space (see Lazarian & Pogosyan 2000;Stanimirović & Lazarian 2001;Chepurnov et al , 2015Padoan et al 2009) (see Lazarian et al 2009, for a review), and in velocity centroids (see Miesch et al 1999;Miville-Deschênes et al 2003).…”
Section: Introductionmentioning
confidence: 99%